Spatial Analysis and Risk Factors for Diabetes Mellitus Type II in Banjarbaru City - Lasari, Hadrianti HD; Musafaah, Musafaah; Afifah, Noor Laili; Mutmainnah, Yulia; Fitriyanti, Jayanti (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
The World Health Organization defines diabetes mellitus as a disease characterized by hyperglycemia and disturbances of carbohydrate, fat and protein metabolism associated with absolute or relative deficiency of insulin action and/or secretion. It is estimated that between 2010 and 2030, developed and developing countries will experience a 20% and 69% increase in the number of adults with diabetes, respectively. This research is a quantitative analytic study with a cross sectional design. Utilizing secondary data at the Health Office of Banjarbaru City as of January-March 2020, in particular the five health centers, namely the South Banjarbaru Health Center, the Sei Besar Health Center, the Sei Ulin Health Center, the Liang Anggang Health Center and the Guntung Manggis Health Center. The sampling method is quota sampling and data analysis using chi square. The result is that there is no relationship between gender (p-value=0.742), marital status (p-value=1), employment status (p-value=0.075), education level (p-value=0.646), smoking (p-value = 0.052), BMI (p-value = 0.451), abdominal circumference (p-value = 0.212), and less fruit and vegetable consumption (p-value = 0.586) on the incidence of diabetes mellitus type II. As for the incidence of diabetes mellitus type II is age (p-value = 0.0001). This study also illustrates the mapping of the distribution of the incidence of Diabetes Mellitus Type II using a color gradation with a scale of 1: 211190, namely in South Banjarbaru District as much as 70.4%, then Liang Anggang District which is 20.4% and North Banjarbaru District 9.2%.